Culture, Lending Relationships, and the Cost of Credit - Albareto, Giorgio; Galardo, Maddalena; Mistrulli, Paolo Emilio; Sorvillo, Bianca (The Review of Corporate Finance Studies, 2022)
We provide evidence on how cultural differences affect loan pricing by using a unique data set from the Italian Credit Register. We show that immigrants pay more for credit compared with natives and that this difference is smaller for immigrants who have Italian parents and for those belonging to the Christian religion. Furthermore, we find that the gap between immigrants and natives narrows as the amount of information shared among lenders through the credit register increases. This suggests that most of the higher cost of credit paid by immigrants is due to statistical discrimination rather than taste-based discrimination. (JEL G21, J15, J71)